Local behavior of Q-homeomorphisms in Loewner spaces - Salimov, R. R.; Салимов, Р. Р.; Салимов, Р. Р. (Institute of Mathematics, NAS of Ukraine, 2008)
We study the problem of the elimination of isolated singularities for so-called Q-homeomorphisms in Loewner spaces. We formulate several conditions for a function Q(x) under which every Q-homeomorphism admits a continuous extension to an isolated singular point. We also consider the problem of the homeomorphicity of the extension obtained. The results are applied to Riemannian manifolds and Carnot groups.